Can We Do More with Less? Analyzing the Organization of Flexibility of Space and Infrastructure at UDCs: A Case Study for Food Center Amsterdam - Rogier Pennings; Bart Wiegmans; Tejo Spit (Logistics)
Background: How can flexible applications of the space and infrastructure of urban distribution centers (UDCs) be organized to help lower demands on space and infrastructure in cities? The application of flexible use of space and infrastructure can improve the efficiency of a UDC, but the challenge lies in the organization of the application of flexibility. Methods: The goal of this research was to identify how flexibility can be organized to impact overall societal benefits for the stakeholders in UDCs. This explorative and qualitative research was applied to the case of Food Center Amsterdam. Results: The results show that stakeholders have a limited understanding of the potential that flexibility can offer; that there is a need for an independent organizing capability and responsibility for collaboration on flexibility; and that a clear way to divide costs, benefits, risks, and opportunities in relation to stakeholder interests is required. Conclusions: Overall, flexibility shows potential to improve the efficient use of infrastructure and space. Further research avenues include the initiation of an organizing capability and distribution method for costs, benefits, risks, and opportunities between stakeholders. The remaining question is, can we get this organized in order to do more with less?